1524. Sex Differences in Influenza: The Challenge Study Experience. (31st December 2020) - Giurgea, Luca; Cervantes-Medina, Adriana; Han, Alison; Czajkowski, Lindsay; Baus, Holly; Memoli, Matthew J
Abstract: Background: Our understanding of the impact of biological sex on influenza-associated disease and the mechanisms that underpin it is still incomplete. Further investigation of sex-linked effects on influenza pathogenesis and clinical outcomes may help tailor vaccine strategies. Animal studies have shown female mice experience more symptoms than male mice during influenza infection. Similarly, human females of reproductive age have higher rates of influenza and influenza-related hospitalizations. However, data is sometimes conflicting and may be confounded by other important differences in baseline characteristics. Human challenge studies have demonstrated the importance of NAI titers as a correlate of protection and may also provide an ideal opportunity to study sex differences in a homogenous group of participants controlled for confounders. Methods: Data from 168 volunteers who underwent Influenza A/California/04/2009/H1N1 challenge studies affiliated with NIAID's LID Clinical Studies Unit were compiled to compare differences between sexes. Participants were included in the analysis if they received a challenge dose of virus of 10 7 TCID50 and were excluded if they had received any vaccines or experimental therapy during the study period. Results: Baseline differences between male and female participants were observed in NAI titers but not HAI titers or age. Outcomes of interest included presence of viral shedding/duration which were similar among sexes. However, symptom number and duration were higher among female participants (p=0.008 and p=0.045 respectively). Ongoing data analysis also shows females have lower post-challenge NAI titers than males. Conclusion: Female participants in our H1N1 challenge studies had more symptoms and a longer duration of symptoms compared to their male counterparts. Differences in NAI titers may potentially explain the observed relationship between sex and symptoms associated with influenza. Disclosures: All Authors : No reported disclosures